Stretching the limits? Strengths and pitfalls of South Atlantic security regionalism - Seabra, P. (Contexto Internacional, 2017)
In the broader context of regional studies, the South Atlantic comes across as a singular, yet still understudied case study for the formation, evolution, and regression of security regionalism dynamics. More so when South Atlantic countries have come to engage in increased regionally focused interactions through wider defence co-operation ties. However, they have also steadfastly eschewed any kind of permanent structures and shared sovereignty over sensitive security issues. This article strives to ascertain the limits and prospects of these regional security dynamics in the South Atlantic. With the focal points set on both South American and African shores, I pinpoint key overtures in this area and question their contribution to advancing an overall regionalisation process. Despite shared threat perceptions and an absence of major intra-regional conflicts, I argue that South Atlantic security regionalism lacks a stable and permanent structure inasmuch as it lacks real autonomy from the dictums of external regional powers, thus leaving the transatlantic space still in flux.